Analisis Penerapan Akuntansi Lingkungan Terhadap Pengelolaan Limbah Pada Rumah Sakit St. Antonius Jopu, Kabupaten Ende - Ngelu, Maria Elvira Ngelu (STIE Madani Balikpapan, 2025)
This study analyzes the application of environmental accounting to waste management at St. Antonius Jopu Hospital, Ende Regency. The purpose of this study is to analyze the application of environmental accounting in waste management and its suitability with the basic framework for the preparation and presentation of financial reports at St. Antonius Jopu Hospital. The type of research used in this study is qualitative research. The type of data used is qualitative data supported by quantitative data. Data collection was obtained from observation, interviews, documentation and literature studies with Miles and Huberman data analysis techniques and using the Nvivo software application tool. This study focuses on the application of environmental accounting and the effectiveness of waste management at St. Antonius Jopu Hospital and its suitability with PSAK 35 and PSAK 57. The results of this study are; (1) The application of environmental accounting at St. Antonius Jopu Hospital has begun but is still not optimal. Identification and recognition of waste costs have been carried out, but are not detailed and are still mixed with other operational costs. Cost measurement is based on estimates without standard methods, and the presentation and disclosure of environmental information is still minimal and less transparent. Therefore, the application of environmental accounting needs to be improved to be more systematic, accurate, and informative. (2) The implementation of environmental accounting at St. Antonius Jopu Hospital is not fully in accordance with the basic framework of financial reporting, because the recognition, measurement, presentation, and disclosure of environmental costs are still not appropriate, objective, and transparent.